Application of the Lok-R Learning Strategy to Science Literacy - Ikhwan Kurniawan; Sarwi Sarwi; Sri Sukasih (Ta'dib, 2023)
This study aims to determine whether or not there is an influence of LOK-R (Literacy, Orientation, Collaboration, Reflection) learning strategies on scientific literacy skills. This type of research includes pre-experimental research with a one-group pre-test and post-test research design. This research was conducted at MI Islamiyah Kalimukti with a sample of 15 students. Data were collected by conducting a pre-test to determine students' initial scientific literacy skills and a post-test to determine the increase in students' scientific literacy abilities after implementing the LOK-R learning strategy. Research data were analyzed using descriptive and quantitative analysis. The n-gain study showed an increase in the average pretest and posttest results. Before implementing the LOK-R learning strategy, the average pretest of students was 56.47; then, it increased to 81.33 in the posttest results of students after implementing the LOK-R learning strategy. Likewise, the paired sample test results obtained a significant value of 0.000 <0.05, which means that H0 is rejected and Ha is accepted. This shows that applying the LOK-R learning strategy increases students' scientific literacy skills. Therefore, the LOK-R learning strategy can be an alternative in science learning activities on heat material and its transfer.